Phase I assessment of safety and therapeutic activity of BAY1436032 in patients with IDH1-mutant solid tumors - Wick, Antje; Bähr, Oliver; Schuler, Martin; Rohrberg, Kristoffer; Chawla, Sant P.; Janku, Filip; Schiff, David; Heinemann, Volker; Narita, Yoshitaka; Lenz, Heinz-Josef; Ikeda, Masafumi; Ando, Yuichi; et al. (Clinical cancer research, 2021)
BAY1436032, an inhibitor of mutant isocitrate dehydrogenase 1 (mIDH1), was active against multiple IDH1-R132X solid tumors in preclinical models. This first-in-human study was designed to determine the safety and pharmacokinetics of BAY1436032, and to evaluate its potential pharmacodynamics and antitumor effects.The study comprised of dose escalation and dose expansion cohorts. BAY1436032 tablets were orally administered twice daily on a continuous basis in subjects with mIDH1 solid tumors.In dose escalation, 29 subjects with various tumor types were administered BAY1436032 across five doses (150-1,500 mg twice daily). BAY1432032 exhibited a relatively short half-life. Most evaluable subjects experienced target inhibition as indicated by a median maximal reduction of plasma R-2-hydroxyglutarate levels of 76%. BAY1436032 was well tolerated and an MTD was not identified. A dose of 1,500 mg twice daily was selected for dose expansion, where 52 subjects were treated in cohorts representing four different tumor types [lower grade glioma (LGG), glioblastoma, intrahepatic cholangiocarcinoma, and a basket cohort of other tumor types]. The best clinical outcomes were in subjects with LGG (n = 35), with an objective response rate of 11% (one complete response and three partial responses) and stable disease in 43%. As of August 2020, four of these subjects were in treatment for >2 years and still ongoing. Objective responses were observed only in LGG.BAY1436032 was well tolerated and showed evidence of target inhibition and durable objective responses in a small subset of subjects with LGG.
Gesehen am 21.02.2022